A new compact and miniaturized multiband uniplanar CPW-fed Monopole antenna with T-slot inverted for multiple wireless applications. Issue 7 (13th February 2017) - Dakir, Rachid; Zbitou, Jamal; Mouhsen, Ahmed; Tribak, Abdelwahed; Sanchez, Angel Mediavilla; Latrach, Mohamed
Abstract : In this paper, the design of a new compact uniplanar coplanar waveguide-fed antenna for multiband wireless application is presented and investigated. This antenna has a compact size of 25 × 25 mm 2 and consists of a three parallel stub optimized added on rectangular slot to the radiator patch and T-shaped which inverted in the ground plane. The final prototype antenna designing resonantes at frequency bands (2.4–2.9 GHz), (3.7–5.2 GHz), and (5.7–6 GHz) with a return loss less than −10 dB. Details of the antenna configuration, design, simulation, and experimental results are presented, investigated, and discussed. The compactness, simple feeding technique, and conception of the uniplanar design make it easy to be integrated within devices of multiples wireless applications.